A critical review of records of alien marine species from the Maltese Islands and surrounding waters (Central Mediterranean) - SCIBERRAS, M.; SCHEMBRI, P.J. (Mediterranean Marine Science, 2007)
An updated list of alien marine species recorded from the Maltese Islands and surrounding waters, compiled from scientific and ‘grey’ literature and from authenticated unpublished reports to the authors, is presented. The listed species are classified in one of four categories as regards establishment status: established, casual, invasive and questionable. Doubtful records are listed as ‘?’. A total of 48 species, including nine dubious ones, are included in the list. Of the accepted records, 64% are established, of which 15.4% are invasive, 18% are casual and 18% are questionable. The most represented groups are molluscs (14 species), fish (13 species) and macrophytes (10 species). Six species are classified as invasive in Maltese waters: Lophocladia lallemandii, Womersleyella setacea, Caulerpa racemosa var. cylindracea, Percnon gibbesi, Fistularia commersonii and Sphoeroides pachygaster; impacts of some of these species on local ecosystems are discussed. Since the early 1900s, there has been an increasing trend in the number of alien marine species reported from the Maltese Islands. Transportation via shipping and in connection with aquaculture, as well as the range expansion of Lessepsian immigrants, appear to be the most common vectors for entry, accounting for 20%, 11% and 32% respectively of the alien species included in this review. The general warming trend of Mediterranean waters and increasing marine traffic may be facilitating the spread of warm-water Atlantic and Indo-Pacific species to the central Mediterranean, including the Maltese Islands.